Payment decoupling and the intra-European calf trade - Sören Prehn; Bernhard Brümmer; Stanley R. Thompson (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2010)
The 2003 reforms of the Common Agricultural policy of the European Union introduced decoupled income transfers as the most prominent policy instrument. However, member states were given substantial discretion over the degree and timing of the reform implementation. As a result, different implementation schemes coexist within the EU, keeping certain parts of the income support coupled to current production levels. This coexistence leads to distortions of production incentives, factor misallocations, and artificial trade flows. Here, we examine these effects in the beef sector where full decoupling was not obligatory for all member states. Based on a cost minimization framework, we derive a sector-specific trade model with heterogeneous firms and quality differences. The model is used to examine the effects of different implementation schemes on intra-European calf trade. Empirical results confirm that the expected distortions to trade flows occured, violating the fundamental CAP principle of Market Unity.
Keywords: F13; F14; Q17; 330; 2003 CAP Reform; Partial Decoupling; Intra-European Calf Trade; Gravity Model; Heterogeneous Firms Trade Model; EU-Agrarpolitik; Agrarreform; Rindfleisch; EU-Binnenhandel; Gravitationsmodell; Schätzung; EU-Staaten